The Application Of Game-Based Learning In Construction Management - Elenany, Yara Ashraf Farouk Moussa (2024)
A Master of Science thesis in Construction Management by Yara Ashraf Farouk Moussa Elenany entitled, “The Application Of Game-Based Learning In Construction Management”, submitted in May 2024. Thesis advisor is Dr. Vian Ahmed. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).